UTAUT 모형을 활용한 AR 오프라인 예술전시 소비자 관람행동 연구 - 유자함(Zi-Han Liu); 김영빈(Young-Bin Kim) (디지털콘텐츠학회논문지, 2023)
본 연구는 AR 오프라인 예술전시를 관람하는 중국 MZ세대 소비자를 설문대상으로, 통합기술수용요인과 AR 오프라인 예술전시의 콘텐츠 품질, 감성반응이 이들의 관람만족도와 재 관람의도에 어떠한 영향을 미치는지를 검토하였다. 결과를 요약하면 다음과 같다. 첫째, 소비자들이 AR 오프라인 예술전시를 관람할 때 영향을 미치는 통합기술수용요인들 중에서 노력기대, 사회적 영향, 촉진조건이 관람만족도에 유의한 영향을 미치는 것으로 밝혀졌다. 반면, 성과기대가 관람만족도에 영향을 미치지 않는 것으로 나타났다. 둘째, AR 오프라인 예술전시의 콘텐츠 품질이 관람만족도에 유의한 영향을 미치는 것으로 밝혀졌다. 반면, AR 오프라인 예술전시에 대한 감성반응이 관람만족도에 영향을 미치지 않는 것으로 나타났다. 셋째, AR 오프라인 예술전시에 대한 소비자들의 관람만족도가 재 관람의도에 긍정적 영향을 미치는 것으로 나타났으며, 관람만족도와 재 관람의도 간의 관계에서 몰입감이 매개효과를 작용하는 것으로 나타났다. This study examines the influence of integrated technology acceptance factors, content quality of exhibited augmented reality (AR) art, and the consumers’ emotional responses to the AR art exhibited on the satisfaction and revisit intentions of MZ-generation consumers attending offline AR art exhibitions. The key findings are as follows: Among the integrated technology acceptance factors affecting the consumers' view of AR offline art exhibitions, the effort expectancy, social influence, and facilitating conditions significantly affect viewer satisfaction. However, the performance expectancy does not significantly influence viewer satisfaction. The content quality in the AR art exhibition significantly affects viewer satisfaction, whereas the emotional response to the AR art exhibition does not have a significant impact. Viewer satisfaction positively influences the intention to revisit an AR offline art exhibition. Immersion plays a mediating role in the relationship between viewer satisfaction and the intention to revisit. KCI Citation Count: 1